Regional Innovation Dilemmatic Policy-Making: between Misconceptions and Missing Conceptions - Santos, Domingos (2020)
Regions are widely recognised as playing a fundamental role in the promotion of the knowledge economy, but most research has been focusing on diagnosing territorial archetypes, their dynamics peculiarities, as well as their drivers of innovation and innovative performance. Less attention has been paid on establishing a linkage between these theoretical foundations and the design of a policy framework and guidelines to promote regional innovation ina systemic way. Based on a vast theoretical research and on the analysis of empirical evidence, the main objective of this article is precisely to discuss this issue in the light of the mainstream theoretical frameworks that enable a better understanding of the relationship innovation-territory, analysing, also, the main criticisms those approaches are arising among some scholars. This article will present a discussion of the main approaches that constitute the theoretical corpus of the so-called territorial innovation models, pointing out to some of their main ambiguities, misconceptions and conceptual gaps and, lastly, will integrate this reflexion into an alternative framework proposal for a new generation of regional innovation policy.